Reliability of the functional threshold power in competitive cyclists - Klitzke Borszcz, F.; Ferreira Tramontin, A.; Pereira Costa, V. (International Journal of Sports Medicine, 2000)
Functional threshold power (FTP) is defined as the highest power that a cyclist can maintain in a quasi-steady state without fatigue for approximately 1 hour. To improve practicality, a 20-minute time-trial test was proposed, where FTP is represented by 95% of the mean power produced. It is preceded by a specific 45-min warm-up, with periods of low intensity, fast accelerations, and a 5-min time-trial. Thus, the aim of this study was to determine the reliability of this protocol, including the reliability of the warm-up, pacing strategy, and FTP determination. For this purpose, 25 trained cyclists performed a familiarization and two other tests separated by seven days. The coefficient of variation (CV [%]), intraclass correlation coefficient (ICC), and change in the mean between test and retest were calculated. The results show that the 20-min time-trial was reliable (CV=2.9%, ICC=0.97), despite a less reliable warm-up (CV=5.5%, ICC=0.84). The changes in the mean between the test and retest were trivial to small for all measurements, and the pacing strategy was consistent across all trials. These results suggest that FTP determination with a 20-min protocol was reliable in trained cyclists.